Linear and nonlinear waves in microstructured solids : homogenization and asymptotic approaches /: homogenization and asymptotic approaches. (2021) - Andrianov, I. V (Igorʹ Vasilʹevich), 1948-; Awrejcewicz, J (Jan); Danishevskiĭ, V. V (Vladislav Valentinovich)
No abstract available